2009
DOI: 10.1073/pnas.0809567106
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy of whole cells in liquid with nanometer resolution

Abstract: Single gold-tagged epidermal growth factor (EGF) molecules bound to cellular EGF receptors of fixed fibroblast cells were imaged in liquid with a scanning transmission electron microscope (STEM). The cells were placed in buffer solution in a microfluidic device with electron transparent windows inside the vacuum of the electron microscope. A spatial resolution of 4 nm and a pixel dwell time of 20 s were obtained. The liquid layer was sufficiently thick to contain the cells with a thickness of 7 ؎ 1 m. The expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
466
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(484 citation statements)
references
References 35 publications
8
466
0
3
Order By: Relevance
“…We are able to examine the dynamics of nanometer-diameter droplets of water in a microfabricated environmental liquid cell that isolates the water sample from the vacuum of a TEM (23)(24)(25). The liquid cell consists of two approximately 20-nm-thick electron translucent Si 3 N 4 membrane windows that are separated and sealed by an approximately 200 nm indium spacer (see SI Text, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We are able to examine the dynamics of nanometer-diameter droplets of water in a microfabricated environmental liquid cell that isolates the water sample from the vacuum of a TEM (23)(24)(25). The liquid cell consists of two approximately 20-nm-thick electron translucent Si 3 N 4 membrane windows that are separated and sealed by an approximately 200 nm indium spacer (see SI Text, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lowloss electron energy loss spectroscopy (EELS) revealed that the liquid layer thickness was typically 500-750 nm at the edges and corners of the SiN window for this spacer configuration 48 . The HAADF-STEM images in Fig 36 and quantum dots 38 , to provide contrast in HAADF-STEM images. In our experiments, the biomineralized magnetite magnetosome chains in cells of M. magneticum act as natural high-contrast labels denoting the position of the bacterial cells.…”
Section: Resultsmentioning
confidence: 99%
“…The controllability of PINEM imaging of biological structures, through the laser pulse polarization and specimen tilting, adds two other dimensions for selectivity in imaging. Currently, we are exploring the use of PINEM to image targeted sites of antibodies with immunolabeling (30) and the possibility of now varying a second time delay to examine dynamics with various specimen preparations, including cryogenic and even possibly biostructures at near-ambient conditions (31). It is also possible to vary the photon wavelength to map different dimensions, to further improve the spatial resolution by near-resonance confinement of the particle field, which is currently of 1-to 2-nm length scale (32), and the energy resolution for mapping all structures at once (33,34).…”
Section: Resultsmentioning
confidence: 99%